Attenuation and Immunogenicity of a Live High Pathogenic PRRSV Vaccine Candidate with a 32-Amino Acid Deletion in the nsp2 Protein. (9th June 2014) - Lu, Wenhui; Sun, Baoli; Mo, Jianyue; Zeng, Xiduo; Zhang, Guanqun; Wang, Lianxiang; Zhou, Qingfeng; Zhu, Ling; Li, Zhili; Xie, Qingmei; Bi, Yinzuo; Ma, Jingyun
Abstract : A porcine reproductive and respiratory syndrome virus (PRRSV) QY1 was serially passed on Marc-145 cells. Virulence of different intermediate derivatives of QY1 (P5, P60, P80, and P100) were determined. The study found that QY1 had been gradually attenuated during the in vitro process. Pathogenicity study showed that pigs inoculated with QY1 P100 and P80 did not develop any significant PRRS clinic symptoms. However, mild-to-moderate clinical signs and acute HP-PRRSV symptoms of infection were observed in pigs inoculated with QY1 P60 and P5, respectively. Furthermore, we determined the whole genome sequences of these four intermediate viruses. The results showed that after 100 passages, compared to QY1 P5, a total of 32 amino acid mutations were found. Moreover, there were one nucleotide deletion and a unique 34-amino acid deletion found at 5′UTR and in nsp2 gene during the attenuation process, respectively. Such deletions were genetically stable in vivo. Following PRRSV experimental challenge, pigs inoculated with a single dose of QY1 P100 developed no significant clinic symptoms and well tolerated lethal challenge, while QY1 P80 group still developed mild fever in the clinic trial after challenge. Thus, we concluded that QY1 P100 was a promising and highly attenuated PRRSV vaccine candidate.